Glutamate Metabotropic Receptor Type 3 (mGlu3) Localization in the Rat Prelimbic Medial Prefrontal Cortex - Woo, Elizabeth; Datta, Dibyadeep; Arnsten, Amy F. T. (Frontiers in Neuroanatomy, 2022)
Metabotropic glutamate receptors type 3 (mGlu3, encoded by GRM3) are increasingly related to cognitive functioning, including the working memory operations of the prefrontal cortex (PFC). In rhesus monkeys, mGlu3 are most commonly expressed on glia (36%), but are also very prominent on layer III dendritic spines (23%) in dorsolateral PFC (dlPFC), where they enhance working memory-related neuronal firing. In contrast, mGlu2 are predominately presynaptic in layer III of macaque dlPFC, indicating a pre- vs. post-synaptic dissociation by receptor subtype. The current study examined the cellular and subcellular localizations of mGlu3 in the rat prelimbic medial PFC (PL mPFC), a region needed for spatial working memory performance in rodents. Multiple label immunofluorescence demonstrated mGlu3 expression in neurons and astrocytes, with rare labeling in microglia. Immunoelectron microscopy of layers III and V found that the predominant location for mGlu3 was on axons (layer III: 35.9%; layer V: 44.1%), with labeling especially prominent within intervaricose segments distant from axon terminals. mGlu3 were also found on glia (likely astrocytes), throughout the glial membrane (layer III: 28.2%; layer V: 29.5%). Importantly, mGlu3 could be seen on dendritic spines, especially in layer III (layer III: 15.6%; layer V: 8.2%), with minor labeling on dendrites. These data show that there are some similarities between mGlu3 expression in rat PL mPFC and macaque dlPFC, but that spine expression enriches and differentiates in the more recently evolved primate dlPFC.